Dietary patterns, foods and nutrients: a descriptive analysis of the systematic reviews conducted to inform the Australian Dietary Guidelines. Issue 1 (11th June 2021) - Wingrove, Kate; Lawrence, Mark A.; McNaughton, Sarah A.
Abstract: Dietary guidelines should be underpinned by the best available evidence on relationships between diet and health, including evidence from nutrient-based, food-based and dietary patterns research. The primary aim of the present study was to analyse the systematic reviews conducted to inform the 2013 Australian Dietary Guidelines according to dietary exposure. The secondary aim was to analyse the reviews by health outcome, and design of included studies. To identify the systematic reviews, the dietary guidelines report was used as a starting point and relevant references were retrieved. The evidence report contained the data used in this analysis. Descriptive statistics were used to analyse reviews according to exposure, outcome, and design of included studies. A total of 143 systematic reviews were included in this analysis. Foods were the most common exposure (86·7 % of reviews), followed by nutrients (10·5 %) and dietary patterns (2·8 %). Chronic disease morbidity and/or mortality was the most common outcome (80·4 %), followed by chronic disease risk factors (19·6 %). Most reviews included evidence from cohort or nested case–control studies (92·3 %), many included evidence from case–control studies (61·5 %) and some included evidence from randomised controlled trials (28·7 %). These results reflect the research questions that were asked, the systematic review methods that were used, and the evidence that was available. In developing future iterations of the Australian Dietary Guidelines, there is an opportunity to review the latest evidence from dietary patterns research.